Implementing a 5-R-Based Waste Management Program to Promote Environmental Sustainability in Dayah - Ratu Fazlia Inda Rahmayani; Erlidawati; T. Meldi Kesuma; Sulastri; Sofia Alfira; Rauzatun Ima; Rahmazani; Siska Fitriani; Furqan; Muhammad Zhaki Ramadhan; Rahmat (Jurnal Pengabdian Bakti Akademisi, 2026)
This community service program aimed to improve awareness and skills in 5R-based waste management-Reduce, Reuse, Recycle, Replace, and Replant-at the Pondok Pesantren Yatim & Dhu’afa of Yayasan Dayah Mini Aceh. The main problem faced by the partner institution was the practice of waste disposal through open burning, which has the potential to cause environmental pollution. The methods applied in this program included socialization, training, mentoring, and hands-on practice in processing waste into useful value-added products, such as compost, eco-enzyme, eco-enzyme-based liquid dishwashing soap, and handicrafts made from plastic waste. The results showed an improvement in students’ knowledge and attitudes toward 5R-based waste management. The average knowledge score increased from 46% before the training to 98% after the training, while positive attitudes toward waste management reached 93.8%. Therefore, this program not only contributed to improving the environmental quality of the dayah but also provided sustainable educational and economic benefits, while supporting the achievement of the Sustainable Development Goals (SDGs).